COMMENTS ON THE OFFENSE SET FORTH UNDER ART. 13IN THE LAW NO. 78/2000 - Mircea Constantin SINESCU; Ionuț-Cristian CARACOTI (Challenges of the Knowledge Society)
The law conditions the application of its provisions only to the arbitrary conduct of the head of a political party, union, employers’ association or some non-profit corporate bodies. Considering the contradictory judgments pronounced so far in case law, we believe that some comments on the capacity of the passive subject against the active subject of an offense are required. In fact, we consider that the dispositions of this article should be conditioned only following some influence exercised on the members of one’s own political party, union, employers’ association or non-profit corporate bodies.